Composite drying aid and application thereof in preparation of fruit powder
By using composite drying aids in microwave drying technology, especially the optimized ratio of starch and maltodextrin, the problems of long drying time, high energy consumption and large nutritional losses are solved, and the rapid, economical and efficient pulp is achieved Preparation of fruit powder protects the anthocyanins and other nutrients in the fruit pulp.
Patent Information
- Application Number
- CN202411662041.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-01-03
AI Technical Summary
The existing microwave drying technology has problems such as long time, high energy consumption, large loss of nutrients and poor drying effect in the preparation of fruit powder by fruit pulp. Especially due to the low glass transition temperature of pectin and fructose, it is difficult to completely remove moisture. .
The optimal ratio was determined by golden ratio by using compound drying agents, including PREGEL-AW1600, PREGEL-AT0705, SPABI-AT0170, SH-52 and HP-CF W0622 starch and maltodextrin. As the second drying aid, it is used for continuous microwave drying after mixing with concentrated fruit pulp.
It significantly increases the drying rate of fruit pulp, protects nutrients such as anthocyanins, forms a uniform gel structure to accelerate water removal, improves drying effect, reduces energy consumption, and meets the requirements of drying and powder making.
Smart Images

Figure BDA0005143671940000061 
Figure HDA0005143671950000011 
Figure HDA0005143671950000012
Abstract
Description
Technical Field
[0001] The invention belongs to the field of food technology, and in particular relates to a drying aid used in preparing fruit powder. Background Art
[0002] Dehydrating the pulp to make powder is an effective way to extend its shelf life; during the drying process, the loss of nutrients should be minimized and production efficiency should be improved. During the drying process, the moisture content of the pulp continues to decrease, the temperature continues to rise, and the ratio of moisture content to temperature (M / T) also continues to decrease; however, as the drying proceeds, the high temperature and low moisture content drying environment easily cause the anthocyanins in the pulp to degrade.
[0003] At present, the commonly used drying means is to use microwave energy as a heat source to dry various materials to remove the moisture in the materials and reduce the moisture content. In order to improve the operating efficiency of microwave drying of fruit pulp to reduce the moisture content, in the process of microwave drying of fruit pulp, an air flow with a fixed wind speed is usually used to take away the moisture dried out from the fruit pulp. The air flow is only used for dehumidification, and the wind speed of the air flow is fixed. It was found in the scientific research process that microwaves will produce corner effects in the fruit pulp during the process of heating and dehydrating the fruit pulp. The trend of cold spots and hot spots and the distribution of moisture content is a distribution state with a high center and a low edge. The temperature distribution trend is an increasing trend from the center to the edge, resulting in a large amount of degradation of the active ingredients of the edge materials. In addition, the use of microwave drying technology currently faces the problems of long time required, high energy consumption, and loss of nutrients. In addition, due to the low glass transition temperature of pectin and fructose substances in the fruit pulp and the state of combination with water, microwave drying is difficult to completely remove the moisture of pure fruit pulp, and it is impossible to meet the drying requirements and achieve the purpose of milling. Therefore, there is an urgent need for a method to achieve rapid dehydration to meet the requirements of dry powder making, while maximally retaining the effective ingredients and ensuring the appearance quality. Summary of the invention
[0004] The invention provides a composite drying aid to solve the problems that the current concentrated fruit pulp cannot be dried and powdered by microwave, and the drying process takes a long time, the drying effect is poor, and nutrients are lost.
[0005] A composite drying aid, wherein the drying aid is PREGEL-AW1600 starch and maltodextrin or PREGEL-AT0705 starch and maltodextrin or SPABI-AT0170 starch and maltodextrin or SH-52 and maltodextrin or HP-CF W0622 and maltodextrin.
[0006] The mass ratio of the PREGEL-AW1600 starch to maltodextrin is 19.1:30.9.
[0007] The mass ratio of the PREGEL-AT0705 starch to maltodextrin is 19.1:30.9.
[0008] The mass ratio of the SPABI-AT0170 starch to maltodextrin is 30.9:19.1.
[0009] The mass ratio of SH-52 to maltodextrin is 11.8:38.2.
[0010] The mass ratio of the HP-CF W0622 to maltodextrin is 30.9:19.1.
[0011] Application of the drying aid in preparing fruit powder.
[0012] A method for preparing fruit powder by concentrating fruit pulp, the method comprising mixing the drying aid described in the claim with concentrated jam, and then preparing the fruit powder by microwave drying.
[0013] The mass ratio of the drying aid to the concentrated jam is 1:1.
[0014] The microwave drying conditions are as follows: microwave power of 17 kW, processing temperature of 70° C., air flow velocity of 1.0 m / s, and drying time of 5 min.
[0015] Beneficial Effects
[0016] 1. In addition to maltodextrin, modified starch is added as the second drying agent in the composite drying aid of this test. It is used for continuous microwave drying to prepare berry fruit powder. Modified starch is a common food additive. It has no risk of allergies, physical discomfort, indigestion, etc., and it also makes the formula fruit pulp easy to shape and dry.
[0017] 2. Maltodextrin and different modified starches were selected as composite drying aids. According to the golden section method, concentrated fruit pulp was added in different mass proportions, and continuous microwave drying equipment was used to carry out drying and powdering tests. The composite drying aid can improve the drying rate of the formulated fruit pulp and protect nutrients such as anthocyanins. The optimal combinations of different modified starch composition formulas are: concentrated fruit pulp: maltodextrin: starch PREGEL-AW1600 = 50: 30.9: 19.1; concentrated fruit pulp: maltodextrin: starch PREGEL-AT0705 = 50: 30.9: 19.1; concentrated fruit pulp: maltodextrin: starch SPABI-A T0170 = 50: 19.1: 30.9; concentrated fruit pulp: maltodextrin: starch SH-52 = 50: 38.2: 11.8; concentrated fruit pulp: maltodextrin: starch HP-CF W0622 = 50: 19.1: 30.9.
[0018] 3. Compare and analyze the effects of different formulas and proportions of drying aids on the powder production effect, and analyze them through low-field nuclear magnetic resonance and Fourier infrared spectroscopy tests. After adding the drying aid, the gel-stable structure is formed to fix the moisture in the fruit pulp, making the moisture distribution more uniform, and there will be no local drying "film formation" that hinders the removal of moisture inside the sample. In addition, the porous structure formed during drying helps to accelerate drying and dehydration; at the same time, the overall Tg of the fruit pulp mixture is increased, so that the binding effect of water molecules is weakened, which is conducive to water evaporation; converting the free water in the fruit pulp into a state between immobile water and bound water is the optimal choice for comprehensive energy consumption and drying effect. And the optimal drying aid additive component is determined to be: hydroxypropyl distarch phosphate (HP-CFW0622), which provides a technical basis for subsequent drying and powder production and improving the nutritional value and economic added value of terminal fruit powder products.
[0019] 4. The technical defect that the microwave drying method cannot dry and powder the fruit pulp has been overcome, and the composite drying aid of the present invention has a good drying effect and is not prone to cause nutritional loss. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] Figure 1 Experimental process for preparing berry fruit powder for continuous microwave drying equipment;
[0021] Figure 2 Schematic diagram of the golden section method, where A and B are the two endpoints of the test range of the golden section method, P1 and P2 are the first test point and the second test point arranged in the test range, respectively, and f(P1) and f(P2) are the test results of the corresponding test points;
[0022] Figure 3 This is a schematic diagram of the distribution of sampling points for measuring fruit powder indicators;
[0023] Figure 4 Schematic diagram of the difficulty in obtaining and grinding the fruit pulp of the experimental point P4M formula after drying;
[0024] Figure 5 This is a comparison of the drying test results with the addition of maltodextrin;
[0025] Figure 6 This is the effect of maltodextrin on the moisture content, anthocyanin content and drying rate of fruit powder;
[0026] Figure 7 This is a comparison of the experimental results of adding pregelatinized starch (PREGEL-AW1600) and maltodextrin as drying aids;
[0027] Figure 8 This is the effect of maltodextrin and pregelatinized starch (PREGEL-AW1600) on the moisture content, anthocyanin content and drying rate of fruit powder;
[0028] Fig. 9 This is a comparison of the experimental results of adding pregelatinized starch (PREGEL-A T0705) and maltodextrin as drying aids;
[0029] Fig.10 This is the effect of maltodextrin and pregelatinized starch (PREGEL-AT0705) on the moisture content, anthocyanin content and drying rate of fruit powder;
[0030] Fig.11 This is a comparison of the test results of adding acetate starch (SPABI-AT0170) and maltodextrin as drying aids;
[0031] Fig.12 This is the effect of maltodextrin and acetate starch (SPABI-A T0170) on the moisture content, anthocyanin content and drying rate of fruit powder;
[0032] Fig.13 This is a comparison of the test results of adding acetylated distarch phosphate (SH-52) and maltodextrin as drying aids;
[0033] Fig.14 This is the effect of maltodextrin and acetylated distarch phosphate (SH-52) on the moisture content, anthocyanin content and drying rate of fruit powder slurry;
[0034] Fig.15 This is a comparison of the test results of adding hydroxypropyl distarch phosphate (HP-CF W0622) and maltodextrin as drying aids;
[0035] Fig.16 This is the effect of maltodextrin and starch (HP-CFW0622) on the moisture content, anthocyanin content and drying rate of fruit powder;
[0036] Fig.17 This is a comparison chart of milling quality with different optimal mass ratios of drying aids;
[0037] Fig.18 The comparison of the effects of different drying aid formulas after the fruit pulp is dried, where a is a schematic diagram showing that the fruit pulp of the test point P4D4 formula is difficult to obtain and grind after drying, and b is a schematic diagram showing that the fruit pulp of the test point P1D5 formula is easy to obtain and grind after drying;
[0038] Fig.19 This is a comparison of Fourier infrared spectra of fruit pulp with different drying agent formulas;
[0039] Fig. 20 This is the comparison result of transverse relaxation time images of fruit pulp with different drying agent formulas;
[0040] Fig.21This is a comparison of glass transition temperature images of fruit pulp with different drying agent formulations. DETAILED DESCRIPTION
[0041] 1. Materials and reagents.
[0042] In this study, red berries were selected as the berries for the experiment. Red berries were purchased from Harbin Xinyue Sanberry Industry Professional Cooperative, and the initial wet basis moisture content was 86.5±0.5%. Red berries with uniform maturity and full grains were selected, removed from impurities, packed, and stored in a -15℃ freezer for later use. Before the experiment, the frozen red berries were taken out of the freezer, sealed and placed in a light-proof room temperature (20±2℃) environment to keep the material temperature close to the room temperature environment. The reagents used in the determination process and the drying aids used in other experiments are shown in Table 1.
[0043] Table 1 Test materials and reagents
[0044] Materials and reagents model Manufacturer Maltodextrin Food Grade Jilin COFCO Biochemical Energy Sales Co., Ltd. Pregelatinized starch PREGEL-AW1600 Hangzhou Prostar Starch Co., Ltd. Pregelatinized starch PREGEL-AT0705 Hangzhou Prostar Starch Co., Ltd. Starch acetate SPABI-AT0170 Hangzhou Prostar Starch Co., Ltd. Acetylated distarch phosphate SH-52 Hangzhou Prostar Starch Co., Ltd. Hydroxypropyl distarch phosphate HP-CFW0622 Hangzhou Prostar Starch Co., Ltd. Ethanol Tianjin Tianli Chemical Reagent Co., Ltd. Analytical grade Distilled water Northeast Agricultural University Water Plant Analytical grade Concentrated hydrochloric acid Tianjin Komiou Chemical Reagent Co., Ltd. Analytical grade acetic acid Tianjin Tianli Chemical Reagent Co., Ltd. Analytical grade Potassium chloride Tianjin Zhiyuan Chemical Reagent Co., Ltd. Analytical grade Anhydrous sodium acetate Sinopharm Chemical Reagent Co., Ltd. Analytical grade Anthocyanin standard sample Tianjin Tianli Chemical Reagent Co., Ltd. UV≥95%
[0045] 2. Test process
[0046] Figure 1The experimental process of preparing berry powder by continuous microwave drying. Weigh the concentrated fruit pulp and drying aid and place them in a blender to mix them for 5 minutes to make a uniform formula fruit pulp. Record the mixing process and the morphology of the formula fruit pulp. Spread the formula fruit pulp evenly on the glass carrier plate and weigh it until it reaches 160g required for the test. The material size is 200mm×200mm. Then place the carrier plate on the conveyor belt of the continuous microwave drying equipment without spacing in sequence. Operate the equipment control panel to set the processing temperature, air flow speed, and conveyor belt transmission speed according to the experimental design. To reduce the error, turn on the magnetron, conveyor belt, and fan in sequence. The formula fruit pulp and the carrier plate start to move in translation under the drive of the conveyor belt. When the formula fruit pulp enters the microwave cavity, start recording the time. When the predetermined drying time is reached (when the predetermined drying time is reached, the formula fruit pulp just leaves the microwave cavity), operate the control panel to turn off the magnetron, conveyor belt, and fan in sequence, quickly take out the carrier plate, and use an infrared thermal imager to capture the temperature image of the formula fruit pulp for subsequent analysis of the temperature distribution law. The dried formula pulp was placed in a space with no air flow to cool down naturally. The temperature of the formula pulp and the indoor temperature were tested with an infrared thermometer. When the temperature difference was ±2°C, the mass was weighed and recorded with an electronic balance. The appearance of the formula pulp was recorded and put into a plastic bag with a specification of 240mm×170mm, and stored in a closed space at room temperature and away from light for subsequent grinding and powder making and index determination. The inner wall temperature and indoor temperature of the cavity of the continuous microwave drying equipment were tested with an infrared thermometer. When the temperature difference was ±2°C, the next set of tests was carried out according to the experimental design. During the test, the concentrated pulp, formula pulp and other spare materials were covered with plastic wrap before the test to prevent water loss. The formula pulp obtained after drying was ground in a water-cooled mill to make berry fruit powder. At the same time, the index was determined according to the experimental design. Each set of tests was repeated 3 times.
[0047] 3. Test methods
[0048] The golden section method is used to select the drying aid component and determine its mass ratio. The golden section method is to divide a line segment into two parts so that the ratio of one part to the total length is equal to 0.618. This segmentation point is called the "golden section point" and this segmentation method is called the golden section. As a mature, reliable and widely used optimization design test method, it can effectively reduce the number of tests, and the test results quickly approach the optimal true value to obtain accurate test data, which is used to determine the optimal formula parameter ratio to achieve the set goals and optimal performance. The specific operation steps of the golden section method are as follows: Figure 2As shown, the first test point P1 is arranged at 0.618 in the test range (the left and right endpoints are A and B respectively), and the corresponding test result f(P1)=S1 is obtained. Then the test point P2 (i.e., 0.382) is set as the second test point at the symmetrical point of P1, and the corresponding test result f(P2)=S2 is obtained. S1 and S2 are compared to select the intervals. According to the principle of "retaining the best and eliminating the worst", the test intervals with poor test results are discarded, and the test intervals with better test results are retained. Then, the above method is used to continue to take the tested symmetrical points in the retained interval for testing, and the "best" is repeatedly taken in the retained part to continue "retaining the best and eliminating the worst", and the range of the test interval is continuously narrowed to seek to optimize the test results until the required accuracy of the test is achieved and the optimal result is obtained.
[0049] Taking the composite drying aid drying test as an example, the specific process of determining the test points in this study is as follows (the relative accuracy of the interval reduction is set to δ1 = 0.06):
[0050] (1) Determination of the first test point P1.
[0051] At point P1, according to the golden ratio, the mass ratio of modified starch is A1=0.618×100%=61.8%, and the mass ratio of maltodextrin is B1=1-A1=0.382×100%=38.2%. At this time, the moisture content of the fruit powder is less than 8% and the anthocyanin content is S1;
[0052] (2) Determination of the second test point P2.
[0053] At point P2, the mass ratio of modified starch is A2=1-A1=0.382×100%=38.2%, and the mass ratio of maltodextrin is B2=1-A2=0.618×100%=61.8%. At this time, the moisture content of the fruit powder is less than 8%, and the anthocyanin content is S2. If S1>S2, consider all the index values comprehensively and discard the part other than the test point P2, and find the symmetrical point P3 of the test point P1 in the remaining segmentation interval;
[0054] (3) Determination of the third test point P3.
[0055] At point P3, the mass ratio of modified starch is A3=A2+0.618×0.618=0.764×100%=76.4%, and the mass ratio of maltodextrin is B3=1-A3=0.236×100%=23.6%. At this time, the moisture content of the fruit powder is less than 8%, and the anthocyanin content is S3. If S1>S3, considering the values of various indicators comprehensively, the part other than the test point P3 is discarded, and the symmetrical point P4 of the test point P1 is found in the remaining segmentation interval;
[0056] (4) Determination of the fourth test point P4.
[0057] At point P4, the mass ratio of modified starch is A4=A3-0.382×0.618=0.528×100%=52.8%, and the mass ratio of maltodextrin is B4=1-A4=0.472×100%=47.2%. At this time, the moisture content of the fruit powder is less than 8%, and the anthocyanin content is S4. If S1>S4, consider all the index values comprehensively and discard the part other than the test point P4, and find the symmetrical point P5 of the test point P1 in the remaining segmentation interval;
[0058] (5) The fifth test point P5 is determined.
[0059] At point P5, the mass proportion of modified starch is A5=A4+0.236×0.618=0.674×100%=67.4%, and the mass proportion of maltodextrin is B5=1-A5=0.326×100%=32.6%. At this time, the moisture content of the fruit powder is less than 8% and the anthocyanin content is S5. If S1>S5, the interval reduction accuracy is 0.056<δ1=0.06, and the first golden section ends. Considering the comprehensive values of various indicators, the best test point of this golden section is determined to be P1.
[0060] 4. Experimental design
[0061] (1) Drying test was carried out by adding maltodextrin as a drying aid.
[0062] This study aims to improve the nutritional value and economic added value of terminal fruit powder products by microwave drying, increase the mass fraction of fruit pulp in the formula fruit pulp (i.e., increase the fraction of effective ingredients), reduce the mass fraction of other added ingredients, refer to the pre-test process effect and test index results, and mix the fruit pulp with maltodextrin (the moisture content is reduced to 78±2%, and the high concentration of fruit pulp is equivalent to increasing the effective ingredients of fruit pulp). The golden section method was used to conduct experiments using continuous microwave drying equipment. The drying conditions were: microwave power 17kW, processing time 5min, processing temperature 70℃, and air flow speed 1m / s. The microwave drying morphology and fruit powder preparation effect were studied. The final moisture content (not higher than 8% according to industry standard NYT1884-2021) and anthocyanin content were used as the standard for selecting the next test point by the golden section to determine the final added ingredients and ratio.
[0063] (2) Drying experiments were carried out by adding modified starch and maltodextrin as composite drying aids.
[0064] In this test, in addition to maltodextrin, modified starch was added as the second drying aid in the composite drying aid. It was used for the test of preparing berry powder by continuous microwave drying. Five modified starches were selected and mixed with maltodextrin as composite drying aids. The purpose of the test was to dry and powder and improve the nutritional value and economic added value of the terminal fruit powder product. In order to increase the mass fraction of the pulp in the formula, the pulp used for mixing with modified starch and maltodextrin (the moisture content was reduced to 78±2%, and the high pulp concentration was equivalent to increasing the effective ingredients of the pulp), but the concentrated pulp fraction was not higher than 50% (if it is higher than 50%, the formula pulp has too much moisture and is not easy to dry). Referring to the effect of the pre-test stirring process and the test index measurement results, this study set the total test volume as 1, the berry concentrated pulp fraction was 50%, and the total mass fraction of the added drying aid was 50%. Five kinds of modified starch were used as drying aids, and continuous microwave drying tests were carried out using the golden section method (drying conditions were the same as those for the single drying aid test) to study the microwave drying morphology and fruit powder preparation effect. The final moisture content, anthocyanin content and other comprehensive indicators were used as the golden section standard for selecting the next test point, and finally the added ingredients and ratios were determined.
[0065] According to the test effects and index results, the effects of different formulas on the quality of berry powder were compared and analyzed. Nuclear magnetic resonance and Fourier infrared tests were used to determine the optimal added ingredients and mass ratio of concentrated fruit pulp.
[0066] 5. The original fruit puree and concentrated fruit puree are prepared.
[0067] Original fruit pulp: put the thawed red raspberries into a high-speed wall breaking machine and beat for 2 minutes to prepare original fruit pulp;
[0068] Concentrated pulp: The original pulp was prepared into concentrated pulp by microwave heating, the process parameters were processing temperature of 68°C, concentration time of 5.4 min, material mass of 4202 g, the air flow velocity was always 0.5 m / s, and the concentrated pulp with a moisture content reduced to 78±2% was obtained. VI. Test index determination and calculation method.
[0069] In order to reduce errors, truly reflect the actual situation of the samples, and make the measured index data more representative, the determination of various test indicators is carried out after grinding and powdering. If the formula pulp still contains too much water after drying and does not meet the conditions for grinding and powdering, attention should be paid to the selection of formula pulp sampling points when measuring the moisture content index. This study uses the "U" shape sampling (such as Figure 3 Except for moisture content, other indicators should be measured according to Figure 3 The samples were freeze-dried and then ground into powder.
[0070] 7. Detection method.
[0071] 1. Determination of anthocyanin content.
[0072] At the end of each test, take out the formula pulp from the outlet of the continuous microwave drying equipment for grinding and powdering (if the water content is too high, press Figure 3 The samples were freeze-dried and powdered as shown), and then the anthocyanin content was determined by pH differential method.
[0073] 2. Determination of moisture content.
[0074] After the test, take out the formula pulp from the outlet of the continuous microwave drying equipment for grinding and powdering (if the water content is too high, press Figure 3 According to GB-5009.3-2016, the samples were dried and weighed, and the measurement was repeated 3 times.
[0075] 3. Determination of color difference value.
[0076] At the end of each test, take out the formula pulp from the outlet of the continuous microwave drying equipment for grinding and powdering (if the water content is too high, press Figure 3 The sample was taken and freeze-dried to make powder as shown in the figure), and the color of the material was directly measured by a fully automatic colorimeter. According to the CIELAB color space, the basic color indicators were expressed as L * 、a * and b * The color value of each group of fruit powder was measured 6 times. The specific calculation formula is as follows. It needs to be compared with the berry original fruit pulp freeze-dried powder. The color difference value (ΔE * ) is measured by the basic color parameters (L * 、a * 、b * ) is calculated according to the formula as follows:
[0077]
[0078] In the formula, Brightness color value of freeze-dried powder of berry pulp before drying;
[0079] The red-green color value of the freeze-dried powder of the berry pulp before drying;
[0080] The yellow-blue color value of the freeze-dried powder of the berry pulp before drying;
[0081] Brightness color value of berry powder product after drying for t time;
[0082] The red-green color value of the berry powder product after drying for t time;
[0083] Yellow-blue color value of berry powder product after drying for t time.
[0084] 4. Determination of temperature.
[0085] In the continuous microwave drying equipment, five infrared temperature sensors are installed on the top of the drying chamber along the center line, arranged in each drying chamber (such as Figure 1 The temperature of the formula pulp during the drying process was measured by an infrared temperature sensor and monitored in real time. The temperature at the entrance and exit of the dryer was measured by a handheld infrared thermometer, and the temperature distribution on the surface of the formula pulp at the exit was measured by an infrared thermal imager. The collected infrared thermal images were processed using FLIRTools software.
[0086] 5. Low-field nuclear magnetic resonance (LF-NMR) analysis.
[0087] Low-field NMR imaging and relaxation curves (water state). Low-field NMR testing was performed using a low-field NMR analyzer.
[0088] 6. Fourier transform infrared spectroscopy (FT-IR) analysis.
[0089] The samples (test points T4, T6, T7, E4 and E7) were freeze-dried into powder using a freeze dryer. 10 mg of sample powder was weighed and pressed into tablets with KBr. The band range was 4000-400 cm -1 , resolution 4cm -1 , the number of scans is 20 times.
[0090] Example 1. Effect of adding maltodextrin on the quality of fruit powder.
[0091] According to the above experimental design and golden section test steps, five test points were set up for five times to achieve the preset relative accuracy δ1 = 0.06. The final moisture content (according to the industry standard NYT1 884-2021, not higher than 8%), anthocyanin content and other comprehensive indicators were used as the golden section to select the next test point, and finally determine the added ingredients and ratio. The mass ratio and index value of the specific formula are as follows Figure 5 .
[0092] According to the experimental design, when the microwave power was 17kW, the processing temperature was 70℃, the air flow velocity was 1.0m / s and the drying time was 5min, the formula pulps with corresponding mass proportions at the five test points were subjected to continuous microwave drying. The results showed that when the mass fraction of the concentrated pulp was high (the mass fractions of the concentrated pulp at the second and fourth test points were 61.8% and 47.2% respectively) and the mass fraction of maltodextrin was low, the moisture content was higher than 8% (10.21% and 8.61% respectively). Although the drying rate of the second test point P2M reached 8.23% / min, due to the concentrated pulp fraction of 61.8%, the moisture content in the formula pulp was high. Even if the concentrated pulp had removed part of the moisture compared with the original pulp, the initial moisture content reached 51.34%. The above test conditions could not dry the moisture to the target moisture content. For example, even though the moisture content of the fourth test point P4M is close to 8%, the formula pulp has a low glass transition temperature after heating and is soft. However, due to the uneven microwave heating, it is partially hard and not suitable for grinding and powdering. Figure 4 As shown. The mass fraction of concentrated pulp at the other three test points was low (the mass fraction of concentrated pulp at the 1st, 3rd and 5th test points was 38.2%, 23.6% and 32.6% respectively), and the mass fraction of maltodextrin was high. The moisture content after drying was 3.74%, 3.29% and 3.46% respectively, all lower than 8%, which can meet the design requirements of the drying and powdering test. This is because maltodextrin has good dispersibility, strong thickening ability and good carrier properties, which has a good effect on improving the drying rate. In addition, maltodextrin can effectively encapsulate the low molecular weight sugar in the fruit juice, reduce the fluid viscosity, improve the drying efficiency, accelerate the dehydration of the formula pulp, and reduce the moisture content of the fruit powder.
[0093] In summary, when maltodextrin is added as a single drying agent, if the mass fraction of concentrated pulp is higher than 50%, the milling index cannot meet the standard requirements of the experimental design. According to the experimental design and the golden section method, the change rules of the index results of each test point are as follows Figure 6 shown.
[0094] Depend on Figure 6It can be seen that the moisture content of the test point P2M is 10.21%, the anthocyanin content is 0.14 mg / g, and the drying rate is 8.23% / min, which are significantly (P<0.05) higher than those of other test points. This is because most of the moisture and all the anthocyanins in the fruit powder come from the concentrated fruit pulp. The higher the mass proportion of maltodextrin, the lower the mass proportion of concentrated fruit pulp, the less moisture in the formula fruit pulp, and the lower the anthocyanin content. After drying under the same conditions, the moisture content, anthocyanin content, and drying rate of the fruit powder decrease with the increase of the mass proportion of maltodextrin; when the maltodextrin mass proportion increases, the moisture content, anthocyanin content, and drying rate of the fruit powder decrease. When the mass proportion of maltodextrin was between 61.8% and 76.4%, there was no significant difference in the moisture content of berry powder (P>0.05); when the mass proportion of maltodextrin was between 52.8% and 61.8% and 67.4% and 76.4%, there was no significant difference in the anthocyanin content of berry powder (P>0.05). This may be because during the microwave drying process, maltodextrin forms a film on the surface of the fruit pulp to protect the anthocyanins from excessive oxidation and thermal degradation, and the higher the added amount, the higher the protection efficiency. However, adding too much maltodextrin will cause the water to be unable to evaporate.
[0095] The specific golden section process is as follows: Due to the effect of maltodextrin, the drying aid can form a film on the surface of the formula pulp during microwave drying at the first test point P1M. During the drying process, bubbles are generated in the formula pulp, which undergoes a large deformation, and a multi-layered bubble wall is formed inside. The formation of bubbles accelerates the drying of the material and makes it dry completely. The moisture content of the second test point P2M is high, and the formula pulp cannot meet the design requirements of the milling test after drying. According to the test design and the golden section method, the part outside the test point P2M is discarded, and the symmetrical point P3M of the test point P1M is found in the remaining segmentation interval to continue the test. The mass fraction of maltodextrin in P3M is as high as 76.4%, and more bubbles are generated while forming a film, and the deformation amplitude is larger. Due to the low fraction of concentrated pulp, the formula pulp has relatively less water content, and the water evaporates quickly, which also shows that the drying aid helps the evaporation of water during microwave drying. The microwave energy absorbed by the material is mainly used to heat up, resulting in that although the overall outer bubble wall formed by the expansion after drying maintains a certain berry color, the internal thin layer is severely burnt, and the anthocyanin is almost completely degraded (only 0.01 mg / g), the color difference value is as high as 30.3, and the nutritional and economic value is extremely low, which is not suitable for actual production. According to the experimental design and the golden section method, the part other than the test point P3M is discarded, and the symmetrical point P4M of the test point P1M is found in the remaining segmentation interval to continue the test. The moisture content of P4M (8.61%) does not meet the requirements of the experimental design standard, so the part other than the test point P4M is discarded, and the symmetrical point P5M of the test point P1M is found in the remaining segmentation interval to continue the test. The anthocyanin content of P5M is 0.01 mg / g, the drying rate is 5.36% / min, and the color difference value is 28.0. The index values are much worse than those of the first test point P1M. Because the addition of drying aids helps the evaporation of water in the formula pulp during the drying process, the microwave energy absorbed by the formula pulp is mainly used for heating after the water evaporates, causing the burning phenomenon.
[0096] In summary, maltodextrin was added as a drying aid in the microwave drying test. The golden section method was used to finally obtain the highest comprehensive index value of the first test point P1M, and the powder making index met the requirements of the experimental design. The formula composition and mass ratio were: concentrated fruit pulp: maltodextrin = 38.2:61.8.
[0097] However, since the mass fraction of concentrated fruit pulp of P1M is only 38.2%, the effective ingredients are relatively few, which reduces the nutritional value and economic value of berry powder. In order to obtain berry powder with high nutritional value recognized by the market, other drying aids were added to the mixture of concentrated fruit pulp and maltodextrin according to the experimental design to improve the powder quality of the formula fruit pulp after drying.
[0098] Example 2. Effect of adding a composite drying aid on the quality of fruit powder.
[0099] 1. Add pregelatinized starch (PREGEL-AW1600) (referred to as starch PAW in this section, represented by D1) and maltodextrin as drying aids.
[0100] According to the above experimental design and golden section method operation steps, five test points were set up for five times to achieve the preset relative accuracy δ1 = 0.06. The final moisture content, anthocyanin content and other comprehensive index effects were used as the golden section standard to select the next test point, and finally determine the added ingredients and ratios. The mass ratio and index values of the specific formula are as follows Figure 7 .
[0101] According to the experimental design, the formula fruit pulp corresponding to the mass ratio of the five test points was continuously microwave dried at a microwave power of 17kW, a processing temperature of 70℃, an air flow velocity of 1.0m / s, and a drying time of 5min. The results showed that the moisture content of each test point after drying was less than 8%, which can meet the requirements of the dry powder test design. According to the experimental design and the golden section method, the change rules of the indicators of each test point are obtained as follows Figure 8 shown.
[0102] Depend on Figure 8 It can be seen that with the increase of maltodextrin content and the decrease of starch PAW content, the moisture content of the formula pulp showed a trend of first decreasing and then increasing. When the ratio of maltodextrin to starch PAW was 67.4:32.6 (P5D1), the moisture content of the formula pulp was as low as 2.5% (P<0.05); while the anthocyanin content and drying rate showed a trend of first increasing and then decreasing. When the ratio of maltodextrin to starch PAW was 61.8:38.2 (P2D1), the anthocyanin content of the formula pulp was as high as 0.23 mg / g (P<0.05). When the ratio of maltodextrin to starch PAW was 67.4:32.6 (P5D1), the drying rate was the highest, reaching 8.14% / min (P<0.05). The main reason for the above situation may be that starch PAW has good solubility and can quickly dissolve in water at low temperature to form a uniform paste-like liquid. The drying process can make the material produce a large number of bubbles, accelerate the drying speed, and make the moisture content of the formula pulp first show a downward trend. However, the heating efficiency inside the microwave cavity is high, which makes starch PAW gelatinized and aged, affecting the evaporation of the moisture in the formula pulp. As the starch PAW content decreases, the drying rate of the formula pulp decreases and the moisture content increases. Starch PAW is not resistant to high temperatures. Therefore, when the moisture content of the formula pulp decreases and absorbs excessive microwave energy to heat up, it will cause scorching (P3D1 and P5D1), and anthocyanins will be degraded in large quantities, resulting in unstable changes in anthocyanins in the formula pulp.
[0103] The specific golden section process is as follows: at the first test point P1D1, due to the combined effect of starch PAW and maltodextrin, the viscosity of the formula pulp is increased, the swelling degree of the formula pulp is increased, a large number of large bubbles are generated during drying, and uniform holes are formed after drying. The formation of bubbles accelerates the dehydration of the material to make it dry completely and easy to grind into powder. At the second test point P2D1, the mass fraction of starch PAW is reduced, and the concentrated formula pulp after drying is easy to make powder. The anthocyanin content is high at 0.23 mg / g. The anthocyanin content of P2D1 is higher than that of P1D1, and the drying rate is similar to that of P1D1. The color difference value after drying is smaller than that of P1D1, and the color is brighter and close to the color of berries. According to the experimental design and the golden section method, the part outside the test point P1D1 is discarded, and the symmetrical point P3D1 of the test point P2D1 is found in the remaining segmentation interval to continue the experiment. Since the mass fraction of maltodextrin in P3D1 is as high as 76.4%, the viscosity of the formula pulp is too high, the deformation amplitude of the formula pulp after drying is larger, and the holes are uneven, and the local hard block is not suitable for grinding and powdering, and the phenomenon of burning occurs. The anthocyanin content of P3D1 is 0.18 mg / g, which is lower than that of P2D1. According to the experimental design and the golden section method, the part outside the test point P3D1 is abandoned, and the symmetrical point P4D1 of the test point P2D1 is found in the remaining segmentation interval to continue the test. The drying rate of P4D1 is 8.01% / min. Due to the fast dehydration speed, the water evaporates quickly, and the microwave energy absorbed by the material is used to increase the temperature, so that the temperature of the berry concentrated formula pulp is too high and the phenomenon of burning occurs. Therefore, the anthocyanin content of P4D1 is reduced to 0.17 mg / g. According to the experimental design and the golden section method, the part outside the test point P4D1 is abandoned, and the symmetrical point P5D1 of the test point P2D1 is found in the remaining segmentation interval to continue the test. The drying rate of P5D1 is slightly lower than that of P2D1, and the anthocyanin content (0.14 mg / g) is less than that of P2D1 in the second test point. This is because the mass proportion of maltodextrin is relatively high, the viscosity of the formula fruit paste is increased, the formation of uneven holes, the local temperature is too high and burnt, and P5D1 is partially hard and lumpy, which is not easy to grind into powder.
[0104] In summary, microwave drying experiments were carried out by adding pregelatinized starch (PREGEL-AW1600) and maltodextrin as drying aids. The golden section method was used to finally obtain the highest comprehensive index value of the second test point P2D1, and the flour making index met the requirements of the experimental design. The formula composition and mass ratio were: concentrated fruit pulp: pregelatinized starch (PREGEL-AW1600): maltodextrin = 50:19.1:30.9.
[0105] 2. Add pregelatinized starch (PREGEL-AT0705) (referred to as starch PAT in this section, represented by D2) and maltodextrin as drying aids.
[0106] According to the above experimental design and golden section method operation steps, five test points were set up for five times to achieve the preset relative accuracy δ1 = 0.06. The final moisture content, anthocyanin content and other comprehensive indicators were used as the standard for selecting the next test point for the golden section, and the added ingredients and ratios were finally determined. The mass ratio and index values of the specific formula are as follows Fig. 9 .
[0107] According to the experimental design, the formula fruit pulp with corresponding mass ratios at 5 test points was continuously microwave dried under the same experimental conditions. The results showed that the moisture content of each test point after drying was less than 8%, which can meet the requirements of the dry powder test design. According to the experimental design and the golden section method, the change rules of the indicators at each test point are obtained as follows Fig.10 shown.
[0108] Depend on Fig.10 It can be seen that with the increase of maltodextrin content and the decrease of starch PAT content, the moisture content and anthocyanin content of the formula pulp showed a downward trend. When the addition amount of pregelatinized starch was between 61.8% and 38.2%, it had no effect on the moisture content and anthocyanin content of the formula pulp. When the content of pregelatinized starch continued to decrease, when the ratio of maltodextrin to starch PAT was 76.4:23.6 (P3D2), the moisture content of the formula pulp was as low as 1.77% (P<0.05), and the anthocyanin content was 0.19 mg / g (P<0.05); the drying rate showed a trend of first decreasing and then increasing. When the ratio of maltodextrin to starch PAT was 76.4:23.6 (P3D2), the drying rate was the highest, reaching 8.29% / min (P<0.05). Because starch PAT has good thermal stability, can maintain consistency and viscosity under high temperature conditions, has good gelling and thickening properties, and can improve the texture and taste of food. When the amount of starch PAT added is too much, it will cause the drying rate to decrease and the water content to be high. This may be because the higher the glucose equivalent of the added starch PAT, the stickier the particles are during the drying process, and the particles are prone to aggregation, which hinders the water transfer between the particles and the drying medium, resulting in low drying rate and high water content; when the mass proportion of starch PAT is reduced, the viscosity of the particles decreases, the drying rate increases rapidly, and the water content decreases rapidly. When the drying time is constant and the microwave energy output is constant, the microwave energy absorbed by the formula pulp is used to increase the temperature in addition to dehydration, causing the formula pulp to heat up rapidly, which in turn causes the thermal degradation of anthocyanins and a decrease in content.
[0109] The specific golden section process is as follows: the first test point P1D2 increases the consistency, viscosity and gelling properties of the formula pulp due to the high mass proportion of starch PAT. After the concentrated pulp is added with the composite drying agent, it is difficult to stir and mix evenly. After the materials are mixed, they are almost rubbery and difficult to spread evenly on the carrier plate. The concentrated formula pulp after drying is crispy and easy to grind into powder. The starch PAT mass fraction of the second test point P2D2 is reduced. It is easy to stir and mix evenly compared with P1D2, easy to powder after drying, and has a higher anthocyanin content of 0.36 mg / g and a smaller color difference of 12.8. The quality index of P2D2 is better than that of P1D2. According to the experimental design and the golden section method, the part outside the test point P1D2 is discarded, and the symmetrical point P3D2 of the test point P2 is found in the remaining segmentation interval to continue the test. The deformation amplitude of P3D2 becomes larger, and uneven holes are formed. This is because the mass fraction of maltodextrin is as high as 76.4%, the viscosity of the formula pulp is too large, and the drying rate reaches 8.29% / min, but the anthocyanin content is 0.19mg / g, which is much lower than P2D2. According to the experimental design and the golden section method, the part outside the test point P3D2 is abandoned, and the symmetrical point P4D2 of the test point P2D2 is found in the remaining segmentation interval to continue the test. The mass fraction of PAT starch in P4D2 is high, and it is not easy to mix evenly. Compared with P2D2, the anthocyanin content is low and the drying rate is similar. According to the experimental design and the golden section method, the part outside the test point P4D2 is abandoned, and the symmetrical point P5D2 of the test point P2D2 is found in the remaining segmentation interval to continue the test. The drying rate of P5D2 is 8.21% / min, and the dehydration speed is fast. After the water evaporates quickly, the microwave energy absorbed by the material is used to increase the temperature, resulting in local over-temperature and burning. The anthocyanin content (0.26 mg / g) and color difference value (13.1) index values are worse than those of the second test point P2D2.
[0110] In summary, microwave drying experiments were carried out by adding pregelatinized starch (PREGEL-AT0705) and maltodextrin as drying aids. The golden section method was used to finally obtain the highest comprehensive index value of the second test point P2D2, and the flour making index met the requirements of the experimental design. The formula composition and mass ratio were: concentrated fruit pulp: pregelatinized starch (PREGEL-AT0705): maltodextrin = 50:19.1:30.9.
[0111] 3. Adding starch acetate (SPABI-AT0170) (referred to as starch SAT in this section, represented by D3) and maltodextrin as drying aids
[0112] According to the experimental design and golden section method operation steps in this chapter, five test points were set up for five times to achieve the preset relative accuracy δ1 = 0.06. The final moisture content, anthocyanin content and other comprehensive indicators were used as the standard for selecting the next test point for the golden section, and the added ingredients and ratios were finally determined. The mass ratio and index values of the specific formula are as follows Fig.11 .
[0113] According to the experimental design, the formula fruit pulp with corresponding mass proportions at 5 test points was continuously microwave dried under the same experimental conditions. The results showed that the moisture content of each test point after drying was less than 8%, which can meet the requirements of the drying and powdering test design. Due to the combined effect of starch SAT and maltodextrin, the viscosity of the formula fruit pulp was appropriately increased. After the concentrated fruit pulp was added with the composite drying agent, each test point was easy to stir and mix evenly, which was convenient for molding and could be evenly spread on the carrier plate. Uniform and tiny bubble holes were formed during the drying process, and the overall deformation of the formula fruit pulp was small. The formation of bubbles accelerated the dehydration of the material to make it dry completely. The concentrated formula fruit pulp after drying was easy to grind into powder, and the drying rate was above 8%. Due to the uniform formation of bubble holes, there was no burning phenomenon during the drying process of most test points. According to the experimental design and the golden section method, the change rules of the indicators of each test point were obtained as follows Fig.12 shown.
[0114] Starch SAT, also known as acetylated starch, is an esterified starch obtained by the reaction of acetic acid or acetic acid derivatives with the hydroxyl groups of starch under certain conditions. Acetate starch is a white powder with low coagulation of starch paste, acid and alkali resistance, high thermal stability and freeze-thaw stability, good transparency, and difficulty in forming hydrogen bonds between molecules. Fig.12As shown in the figure, with the increase of maltodextrin content and the decrease of starch SAT content, the moisture content of the formula pulp showed a downward trend. When the starch SAT addition amount was between 76.4% and 61.8%, the moisture content of the formula pulp did not change significantly. When the starch SAT content continued to decrease, when the ratio of maltodextrin to starch SAT was 47.2:52.8 (P4D3), the moisture content of the formula pulp was as low as 3.40% (P<0.05); while the anthocyanin content and drying rate showed a trend of first decreasing, then increasing, and then decreasing. When the ratio of maltodextrin to starch SAT was 38.2:61.8 (P1D3), the anthocyanin content was the highest, reaching 0.37 mg / g (P<0.05). As the content of starch SAT decreased, hydrogen bonds were formed between molecules, encapsulating anthocyanin, improving its thermal stability and effectively preventing degradation. When the ratio of maltodextrin to starch SAT was 47.2:52.8 (P4D3), due to the fast drying rate and low water content of the formula pulp, the microwave energy absorbed by the material was used to increase the temperature (reaching 115.8℃), and anthocyanin was degraded in large quantities, with a content of only 0.25 mg / g. Different addition amounts of starch SAT had no significant effect on the drying rate (P>0.05). This is because an acetyl group with steric hindrance was connected to the molecule of starch SAT, which weakened the association of hydrogen bonds and significantly reduced the gelatinization temperature, so it could not promote the drying rate of the formula pulp.
[0115] The specific golden section process is as follows: the drying rates of the first test point P1D3 and the second test point P2D3 are similar, and the anthocyanin content of P1D3 is higher (0.37 mg / g) and the color difference value is smaller (13.2). According to the experimental design and the golden section method, the test point P2D3 is discarded, and the symmetrical point P3D3 of the test point P1D3 is found in the remaining segmentation interval to continue the test. After drying, the anthocyanin content of P3D3 is 0.32 mg / g and the drying rate is 8.21% / min, which are lower than those of P1D3. At the same time, the color difference value is 14.9 and is also larger. According to the experimental design and the golden section method, the test point P3D3 is discarded, and the symmetrical point P4D3 of the test point P1D3 is found in the remaining segmentation interval to continue the test. Compared with P1D3, the anthocyanin content and drying rate of P4D3 are reduced, and the color difference value is greatly increased. According to the experimental design and the golden section method, the test point P4D3 is discarded, and the symmetrical point P5D3 of the test point P1D3 is found in the remaining segmentation interval to continue the test. The anthocyanin content of P5D3 was 0.25 mg / g, which was less than that of the first test point P1D3.
[0116] In summary, the microwave drying test was carried out by adding acetate starch (SPABI-AT0170) and maltodextrin as drying aids. The golden section method was used to finally obtain the highest comprehensive index value of the first test point P1D3, and the milling index met the requirements of the experimental design. The formula composition and mass ratio were: concentrated pulp: acetate starch (SPABI-AT0170): maltodextrin = 50:30.9:19.1.
[0117] 4. Add acetylated distarch phosphate (SH-52) (referred to as starch SH in this section, represented by D4) and maltodextrin as drying aids.
[0118] According to the experimental design and golden section method operation steps in this chapter, five test points were set up for five times to achieve the preset relative accuracy δ1 = 0.06. The final moisture content, anthocyanin content and other comprehensive indicators were used as the standard for selecting the next test point for the golden section, and the added ingredients and ratios were finally determined. The mass ratio and index values of the specific formula are as follows Fig.13 .
[0119] According to the experimental design, the formula fruit pulp of the corresponding mass ratio of the five test points was continuously microwave dried under the same experimental conditions. The moisture content of each test point after drying was less than 8%, which could meet the moisture requirements for powder making. In addition, due to the combined effect of starch SH and maltodextrin, the viscosity of the formula fruit pulp was appropriately increased. After the concentrated fruit pulp was added with the composite drying agent, each test point was easy to stir and mix evenly, and it was easy to shape and evenly spread on the carrier plate. Uniform bubbles were formed during the drying process. The formation of bubbles accelerated the dehydration of the material to make it dry completely, and it was easy to grind into powder after drying. Due to the uniform formation of bubbles, no burning phenomenon occurred during the drying process of most test points. However, during the golden section process, the mass proportion of maltodextrin in the fourth test point P4D4 was too high, reaching 85.4%. The viscosity of the formula pulp was too high, and a large number of large bubbles were generated during the drying process. The deformation amplitude was large after drying, resulting in uneven holes, causing local temperature to be too high and burnt. The anthocyanin content was low at 0.3 mg / g, the color difference value was too large at 17.1, and some materials were blocky particles, which were very hard and not suitable for grinding. Figure 4 As shown. The experimental design and golden section method obtained the change rules of the indicators at each test point as shown Fig.14 shown.
[0120] Starch SH is an esterified cross-linked composite modified starch obtained by acetylation and phosphate reaction of native starch. It has the characteristics of good film-forming property, good fluidity, high thermal stability and strong acid resistance. Fig.14As shown in the results, with the increase of maltodextrin content and the decrease of starch SH content, the moisture content and anthocyanin content of the formula pulp first decreased and then increased. When the ratio of maltodextrin to starch SH was 70.8:29.2 (P5D4), the moisture content of the formula pulp was as low as 3.18% (P<0.05); when the ratio of maltodextrin to starch SH was 76.4:23.6 (P3D4), the anthocyanin content was the highest, reaching 0.36 mg / g (P<0.05); while the drying rate showed a downward trend. When the ratio of maltodextrin to starch SH was 38.2:61.8 (P1D4), the drying rate was the fastest, reaching 8.2% / min (P<0.05). This is because the source and degree of starch modification will cause differences in the average swelling particle size and water absorption capacity, thereby affecting the drying effect.
[0121] The specific golden section process is as follows: the drying rates of the first test point P1D4 and the second test point P2D4 are similar, and the anthocyanin content of P2D4 is higher (0.32 mg / g). According to the experimental design and the golden section method, the part outside the test point P1D4 is discarded, and the symmetrical point P3D4 of the test point P2D4 is found in the remaining segmentation interval to continue the test. The anthocyanin content of P3D4 is 0.36 mg / g, which is higher than P2D4, the drying rate is slightly lower, and the color difference value is smaller than P2D4. According to the experimental design and the golden section method, the part outside the test point P2 starch SH is discarded, and the symmetrical point P4D4 of the test point P3D4 is found in the remaining segmentation interval to continue the test. Compared with P3D4, P4D4 has a lower anthocyanin content, a slightly higher drying rate, a significantly increased color difference value, and is not easy to grind and powder. According to the experimental design and the golden section method, the part outside the test point P4D4 is discarded, and the symmetrical point P5D4 of the test point P3D4 is found in the remaining segmentation interval to continue the test. The drying rate of P5D4 reached 8.11% / min, and the dehydration speed was fast. After the water evaporated quickly, the microwave energy absorbed by the material was used to increase the temperature, resulting in local over-temperature and burning. The anthocyanin content was 0.25 mg / g and the color difference value was 17.1. The index values were worse than those of the third test point P3D4.
[0122] In summary, acetylated distarch phosphate (SH-52) and maltodextrin were added as drying aids to carry out microwave drying experiments. The golden section method was used to finally obtain the highest comprehensive index value of the third test point P3D4, and the flour making index met the requirements of the experimental design. The formula composition and mass ratio were: concentrated pulp: acetylated distarch phosphate (SH-52): maltodextrin = 50:11.8:38.2.
[0123] 5. Add hydroxypropyl distarch phosphate (HP-CF W0622) (referred to as starch HCW in this section, represented by D5) and maltodextrin as drying aids.
[0124] According to the experimental design and golden section method operation steps in this chapter, five test points were set up for five times to achieve the preset relative accuracy δ1 = 0.06. The final moisture content, anthocyanin content and other comprehensive indicators were used as the standard for selecting the next test point for the golden section, and the added ingredients and ratios were finally determined. The mass ratio and index values of the specific formula are as follows Fig.15 .
[0125] According to the experimental design, the formula fruit pulp with corresponding mass proportions at 5 test points was continuously microwave dried under the same experimental conditions. The results showed that the moisture content of each test point after drying was less than 8%, which can meet the requirements of the drying and powdering test design. Due to the combined effect of starch HCW and maltodextrin, the viscosity of the formula fruit pulp was appropriately increased. After the concentrated fruit pulp was added with the composite drying agent, each test point was easy to stir and mix evenly, and it was easy to shape and evenly spread on the carrier plate. Uniform and tiny bubble holes were formed during the drying process, and the overall shape of the formula fruit pulp became smaller. The formation of bubbles accelerated the dehydration of the material to make it dry completely. After drying, the formula fruit pulp was easy to grind into powder, and the drying rate was above 8.10%. According to the experimental design and the golden section method, the change rules of the indicators of each test point were obtained as follows Fig.16 shown.
[0126] Starch HCW is a type of modified starch that is double-modified by hydroxypropyl etherification and cross-linking. It has excellent properties such as resistance to mechanical processing, high temperature resistance, and good stability. It can be used as a food stabilizer and thickener and is widely used in the food field. Fig.16It can be seen that with the increase of maltodextrin content and the decrease of starch HCW content, the moisture content of the formula pulp showed a downward trend. When the addition amount of starch HCW was between 67.4% and 38.2%, there was no significant difference in the moisture content of the formula pulp (P>0.05). This may be due to the hydrogen bond interaction between hydroxypropyl and water, which enhanced the stability of the starch structure and made it difficult for the moisture in the formula pulp to evaporate. The anthocyanin content and drying rate of the formulated fruit pulp showed a trend of first increasing and then decreasing. When the ratio of maltodextrin to starch HCW was 32.6:67.4 (P5D5), the drying rate was the highest, reaching 8.23% / min; when the ratio of maltodextrin to starch HCW was 38.2:61.8 (P1D5), the anthocyanin content was the highest, reaching 0.41 mg / g. On the one hand, it may be due to the combination of starch HCW with the pectin molecules in the formulated fruit pulp, the presence of hydroxypropyl increased the steric hindrance, the cross-linking bond enhanced the hydrogen bond strength between the pectin molecules, stabilized the spatial structure of pectin, and inhibited the thermal loss of anthocyanin content to a certain extent. On the other hand, due to the correlation between anthocyanin content and moisture content, anthocyanin is extremely susceptible to nucleophilic attack by water molecules, and 2-phenylbenzopyran cation is hydroxylated and degraded. When the moisture content decreases, the anthocyanin content increases. However, since the temperatures at test points P4D5 and P2D5 were too high (reaching 116.4°C and 117.6°C, respectively), the anthocyanin degradation content decreased when the addition amount of starch HCW was between 61.8% and 38.2%.
[0127] The specific golden section process is: after the first test point P1D5 and the second test point P2D5 are dried, P1D5 has a higher anthocyanin content (0.41 mg / g), a faster drying rate (8.21% / min), a smaller color difference value (12.2), and the formula fruit pulp of P1D5 forms a micro-pore structure and is evenly distributed, with a fast dehydration speed, and remains crisp under high temperature conditions. This is because the starch HCW and maltodextrin work together to increase the glass transition temperature of the formula fruit pulp. All indicators of P1D5 are better than P2D5. According to the experimental design and the golden section method, the part other than the test point P2D5 is discarded, and the symmetrical point P3D5 of the test point P1D5 is found in the remaining segmentation interval to continue the experiment. After drying, the anthocyanin content of P3D5 was 0.31 mg / g, and the drying rate was 8.15% / min, which were slightly lower than P1D5. The color difference value was 12.5, which was greater than P1D5. According to the experimental design and the golden section method, the part other than the test point P3D5 was abandoned, and the symmetrical point P4D5 of the test point P1 was found in the remaining segmentation interval to continue the test. Compared with P1D5, the anthocyanin content of P4D5 was lower, the drying rate was slightly higher, and the color difference value was greatly increased. According to the experimental design and the golden section method, the part other than the test point P4D5 was abandoned, and the symmetrical point P5D5 of the test point P1D5 was found in the remaining segmentation interval to continue the test. The anthocyanin content of P5D5 is 0.35 mg / g and the color difference value is 16.0. Both index values are worse than those of the first test point P1D5. This is because the drying speed is fast (reaching 8.23% / min). After the water evaporates quickly, the microwave energy absorbed by the material is used to increase the temperature. The temperature inside the formula pulp is too high, resulting in a small amount of burning, anthocyanin degradation, and a larger color difference value.
[0128] In summary, microwave drying experiments were carried out by adding hydroxypropyl distarch phosphate (HP-CF W0622) and maltodextrin as drying aids. The golden section method was used to finally obtain the highest comprehensive index value of the first test point P1D5, and the milling index met the requirements of the experimental design. The formula composition and mass ratio were: concentrated pulp: hydroxypropyl distarch phosphate (HP-CF W0622): maltodextrin = 50:30.9:19.1.
[0129] Example 3. Comparison of the effects of different composite drying aids on flour quality.
[0130] According to the above experimental design, the concentrated fruit pulp was subjected to microwave drying tests with single drying aid and different composite drying aids using the golden section method, and the optimal mass ratio of different drying aids was obtained based on a comprehensive analysis of the measured indicators. The results showed that different combinations of drying aids had a great influence on the quality of the prepared fruit powder. The specific drying aid formula ratio and indicators were as follows: Fig.17 As shown:
[0131] according to Fig.17It can be seen from the data that six different combinations of drying aids are added to the concentrated fruit pulp in the optimal mass ratio. After continuous microwave drying, the formula corresponding to the test point P1M has a concentrated fruit pulp mass fraction of only 38.2%, so the anthocyanin content is 0.06 mg / g, the nutrients and effective ingredients are too few, the economic value of the produced fruit powder is low, and this formula is not suitable for actual production. The mass fraction of the concentrated fruit pulp of the other five formulas is 50%. After drying under the same test conditions, the anthocyanin content of the P1D5 formula is the highest at 0.41 mg / g, and the drying rate is also the fastest at 8.21% / min. At the same time, the color difference value and the average temperature of the discharge port are also the best values compared with other formulas. In addition, during the test, the P1D5 formula is easy to mix evenly, and the whole process is the most convenient to operate. It is easy to shape and spread evenly on the loading tray, and it is easy to take out from the loading tray after drying (such as Fig.18 Compared with a and b), it is easy to grind and powder, and there is no residual material in the loading plate, the formula fruit pulp is fully utilized, there is no loss or waste of raw materials, it is easy to save costs, improve the utilization rate of raw materials, and is suitable for actual processing and production.
[0132] Example 4. Analysis of the mechanism of microwave milling of concentrated fruit pulp with the addition of a composite drying agent.
[0133] Based on the above study comparing the effects of different combinations of drying aids on powder quality, the P1M formula is not suitable for actual production because of the low effective ingredients. This section uses LF-NMR and FT-IR tests to analyze the mechanism of the other five formulas with a mass fraction of 50% concentrated fruit pulp to explore the effects of different combinations of drying aids on the preparation of berry powder by continuous microwave drying.
[0134] like Fig.19 As shown, this study analyzed the changes in the intermolecular forces between the drying aid and the concentrated fruit pulp water through the Fourier transform infrared spectra of the original fruit pulp, concentrated fruit pulp and the formulated fruit pulp after adding different drying aid formulations.
[0135] pass Fig.19 It can be seen that the spectrum of the original pulp is at 3000cm -1 and 3600cm -1 There is a broad absorption peak between 3400cm -1 The strong characteristic peak near 2920cm corresponds to the OH stretching vibration. -1 The characteristic peak at 1624 cm indicates the antisymmetric stretching vibration of CH2. -1 The characteristic peak at 1738cm represents C=C stretching. -1 The characteristic peak observed at 1420 cm represents the C=O stretching vibration of the carboxylic acid group, which is related to the acetylated structure on the anthocyanin sugar residue. -1The transition band at 1053 cm-1 can be attributed to CN stretching and NH bending vibrations. -1 The characteristic peak at represents the COC stretching vibration of the aromatic ring.
[0136] The original pulp and the concentrated pulp have similar characteristic peaks, which indicates that no new bonds or functional groups are formed in the pulp after microwave heating. Compared with the original pulp and the concentrated pulp, the pulp with drying aid has a higher peak at 3060-3680cm -1 The OH vibration peak at the wave number ranges from 3408.56 to 3419.65 cm -1 Increased to 3427.85~3451.00cm -1 , indicating that after adding the drying aid, hydrogen bonds were formed between the hydroxyl groups of the fruit pulp and the drying aid, and a stable complex was formed between the fruit pulp and the drying aid through hydrogen bonds. In addition, due to the hydrogen bonds formed between the fruit pulp and the drying aid, the fruit pulp at 1624cm -1 The peak at 1648 cm -1 The peak shift and peak change of the formulated fruit pulp after adding the drying agent indicate that a covalent network is formed between the fruit pulp and the drying agent through chemical adsorption. Therefore, FTIR confirms the covalent interaction between the fruit pulp and the drying agent.
[0137] 1053cm -1 、1420cm -1 、1738cm -1 It is an important characteristic peak of flavonoids. These wavelengths are closely related to the structure of anthocyanins. -1 The characteristic peak wavelength is reduced to 1022cm -1 , 1420cm -1 The characteristic peak at 1738cm -1 The peak value of the characteristic peak at 100° is reduced, indicating that the active substances such as anthocyanins in the fruit pulp are embedded in the internal structure of the drying aid, thereby improving the stability. Therefore, after adding the drying aid, the formula fruit pulp has a higher anthocyanin content after drying.
[0138] This study analyzes the water binding state of concentrated fruit pulp and drying aids through the transverse relaxation time curves of original fruit pulp, concentrated fruit pulp and formula fruit pulp after adding drying aids. The transverse relaxation time of the original berry fruit pulp shows three relaxation periods (three different peaks) from left to right, representing three different water states: bound water, immobile water and free water. The larger the transverse relaxation time, the higher the water freedom.
[0139] like Fig. 20As shown in the figure, in the T2 spectrum, after the concentrated pulp is added with the drying aid, the drying aid will mix with the water in the pulp to form a gel-like structure, which will cause the water in the formula pulp to be redistributed among the three forms of bound water, immobile water and free water. Compared with the concentrated pulp, the T2 peak of the formula pulp begins to shift to the left, indicating that the addition of the drying aid reduces the fluidity and freedom of the water inside the formula pulp. This is because after the addition of the drying aid, hydrogen bonds are formed between the hydroxyl groups of the pulp and the drying aid, and they are connected to form a stable complex, which shows an overall trend of water with high freedom to water with low freedom.
[0140] Fig. 20 In the experiment, the T2 peaks of test points P2D1 and P3D4 shifted to the left with a large amplitude, indicating that the water freedom degree of the formulas corresponding to the two test points was the lowest and bound water; the signal amplitude was high, indicating that bound water dominated the moisture content of the two formulas. During microwave drying, the bound water was relatively stable and difficult to remove, so the drying rate of the two test points was low; the embedding protection effect of the two starches and maltodextrin was not good, and the anthocyanin stability was not strong and the content was low. The T2 peak trajectories of test points P2D2 and P1D3 were repeated, the left shift amplitude was small, and the signal amplitude was divided into two peaks, indicating that the overall water binding state of the corresponding two formulas was almost the same, the degree of freedom was less reduced, and the internal moisture was divided into bound water and immobile water, among which the immobile water signal amplitude was relatively high and the content was high. During microwave drying, the immobile water part of the moisture in the two formulas was relatively unstable and easy to remove, so the drying rate was high; the embedding protection effect of the two starches and maltodextrin was good, and the anthocyanin stability was strong and the content was high.
[0141] Fig. 20 The left shift amplitude of the T2 peak of the test point P1D5 is relatively centered, which is in the transition stage between bound water and immobile water, and there is no obvious boundary, indicating that most of the water freedom degrees in the formula corresponding to this test point are between bound water and immobile water, and the overall stability is relatively moderate. This formula has a high drying rate and the highest anthocyanin content during continuous microwave drying, which is due to the better embedding protection effect of hydroxypropyl distarch phosphate (HP-CF W0622) and maltodextrin as drying aids.
[0142] Although the addition of drying aids leads to a decrease in free water, thereby slowing down the dehydration rate in the initial stage of drying, the gel system formed after adding starch helps the sample to be further dried and dehydrated in the future, so that it can meet the requirements of powder making. Because the gel-stable structure formed by starch and the water in the pulp can fix the water in the pulp, make the water distribution with high degree of freedom more uniform, reduce the excessive drying speed of the sample surface, and prevent local drying or uneven moisture. This prevents the phenomenon of "film formation" caused by too low surface moisture and hindering the removal of moisture inside the sample. The stable structure formed by hydrogen bonding between the pulp and the drying aid forms a uniform porous structure during microwave drying, which accelerates the drying and dehydration rate. However, too much bound water will increase the energy consumption of dehydration. Therefore, converting the free water in the pulp into a water content between immobile water and bound water is the best choice for comprehensive energy consumption and drying effect. Hydroxypropyl distarch phosphate (HP-CF W0622) and maltodextrin as drying aids make most of the water degrees of freedom of the formula pulp between bound water and immobile water, which confirms that the final selected drying aid and mass ratio are the optimal formula.
[0143] In addition, during the continuous microwave drying process, since berries contain a large amount of glucose, fructose, and pectin, their glass transition temperature T g The temperature rises during drying, making the concentrated pulp viscous, which strengthens the binding effect on water molecules and forms a dense film structure on the surface, which is very unfavorable for the evaporation of water. The addition of drying aids improves the overall T of the formula pulp. g , which weakens the binding effect of water molecules and is conducive to water evaporation.
[0144] Example 5. Changes in Tg.
[0145] This study used the differential scanning calorimeter test results of original fruit pulp, concentrated fruit pulp, and formulated fruit pulp with drying aid added (all of which were prepared by freeze-drying method for fruit powder testing) to analyze the glass transition temperature T after the concentrated fruit pulp and drying aid were combined. g Changes in situation.
[0146] like Fig.14 As shown in the figure, compared with the original pulp and concentrated pulp, the endothermic peak of the pulp after adding drying aid obviously moves to the higher temperature direction. g The lowest is only 4.00℃, the original pulp glass transition temperature T g The lowest temperature was 8.36℃, which caused the fruit powder obtained by freeze-drying the original fruit pulp and concentrated fruit pulp to quickly turn into a viscous state at room temperature; and the addition of drying aids significantly increased the overall T g value (48.55~54.85℃), among which the T g The highest temperature reached 54.85℃.
[0147] During the continuous microwave drying process, the original berries contain a large amount of glucose, fructose and pectin, and their glass transition temperature T g The drying temperature is low, and the free water in the pulp is quickly removed. The pulp concentration increases, T g Decline. With T g The fruit pulp becomes viscous when heated, and the binding effect on water molecules is enhanced. A dense film structure is formed on the surface, which is very unfavorable for the evaporation of water, resulting in the fruit pulp cannot be directly dried into powder. g The T value of the fruit powder system can be increased by adding polysaccharides with larger molecular weight such as starch. g After the concentrated fruit pulp is added with the drying aid, it is equivalent to adding macromolecules to the concentrated fruit pulp, and the fruit pulp and the drying aid are connected by hydrogen bonds to form a stable structure, which makes the T g The value increases.
[0148] Recipe Fruit Puree T g The value increases, which significantly weakens the binding effect of water molecules, facilitates the evaporation of water, and finally achieves the purpose of drying and powdering. g The highest, the highest drying efficiency and the best effect, further confirmed that concentrated pulp: maltodextrin: hydroxypropyl distarch phosphate (HP-CF W0622) is the optimal formula.
Claims
1. A composite drying aid, characterized in that: The drying aid is PREGEL-AW1600 starch and maltodextrin or PREGEL-AT0705 starch and maltodextrin or SPABI-AT0170 starch and maltodextrin or SH-52 and maltodextrin or HP-CF W0622 and maltodextrin.
2. The drying aid according to claim 1, characterized in that: The mass ratio of the PREGEL-AW1600 starch to maltodextrin is 19.1:30.
9.
3. The drying aid according to claim 1, characterized in that: The mass ratio of the PREGEL-AT0705 starch to maltodextrin is 19.1:30.
9.
4. The drying aid according to claim 1, characterized in that: The mass ratio of the SPABI-A T0170 starch to maltodextrin is 30.9:19.
1.
5. The drying aid according to claim 1, characterized in that: The mass ratio of SH-52 to maltodextrin is 11.8:38.
2.
6. The drying aid according to claim 1, characterized in that: The mass ratio of the HP-CF W0622 to maltodextrin is 30.9:19.
1.
7. Use of the drying aid according to claim 1 in the preparation of fruit powder.
8. A method for preparing fruit powder by concentrating fruit pulp, characterized in that: The method comprises mixing the drying aid according to claim 1 with concentrated fruit pulp, and then preparing fruit powder by microwave drying.
9. The method according to claim 8, characterized in that: The mass ratio of the drying aid to the concentrated fruit pulp is 1:
1.
10. The method according to claim 8, characterized in that: The microwave drying conditions are as follows: microwave power of 17 kW, processing temperature of 70° C., air flow velocity of 1.0 m / s, and drying time of 5 min.